Transforming growth factor beta 1 (TGFβ1) plasmatic levels and haplotype structures in obesity: a role for TGFβ1 in steatosis development - Felicidade, Ingrid [UNESP]; Bocchi, Mayara; Ramos, Marília Rizzon Zaparolli; Carlos, Ligia de Oliveira; Wagner, Nathalia Ramori Farinha; Campos, Antônio Carlos Ligocki; Ribeiro, Lúcia Regina [UNESP]; Mantovani, Mário Sérgio; Watanabe, Maria Angelica Ehara; Vitiello, Glauco Akelinghton Freire (Springer Nature, 2021)
Background: Obesity is considered a chronic inflammatory disease and transforming growth factor beta 1 (TGFβ1) might exert important roles in disease pathogenesis regulating adipocyte differentiation and immune-inflammatory environment. However, the role of this cytokine as a biomarker in obesity is poorly addressed. Therefore, the present study aimed to evaluate the impact of TGFB1 polymorphisms and TGFβ1 plasmatic levels in obesity Methods and results: TGFB1 promoter region polymorphisms (rs1800468, G-800A and rs1800469, C-509 T) were evaluated in 75 obese patients and 45 eutrophic patients through PCR–RFLP and plasmatic TGFβ1 was quantified through ELISA from 37 of the obese patients, and correlations with clinical and biochemical parameters were tested. Despite no association was found between TGFB1 polymorphisms and obesity susceptibility, several correlations with clinical data were noted. Among others, AC haplotype negatively correlated with plasmatic TGFβ1, while plasmatic TGFβ1 negatively correlated with C-reactive protein and positively correlated with liver abnormalities on ultrasound and, specifically, with steatosis presence and degree. Conversely, GT haplotype, which associates with higher TGFβ1 production, was also positively correlated with the same parameters of liver abnormalities. Further, plasmatic vitamin D negatively correlated with TGFβ1, while positively correlated with AC haplotype. Conclusion: Overall, the results indicate that TGFβ1 might exert important roles in obesity pathophysiology and correlate with biochemical and clinical parameters both at systemic protein as well as at genetic level. Importantly, the consistent positive correlation at both levels with steatosis might suggest this cytokine as a biomarker for this hepatic abnormality in obese patients.
Keywords: Inflammation; Obesity; Overweight; Steatosis; Transforming growth factor beta